MENINGKATKAN KESEJAHTERAAN SOSIAL MASYARAKAT BERBASIS MANAJEMEN MASJID: STUDI PADA MASJID BESAR AL-ISLAH KRAGAN REMBANG - Muhyiddin, Ahmad Shofi; Umam, Badrul (UIN Sunan Kalijaga, 2023)
This study aims to describe and analyze the efforts of Al-Islah Grand Mosque of Kragan Village in improving community welfare through mosque management. A qualitative research method conducted involving nine subjects, including the chairman of the takmir, vice chairman of the takmir, secretary, kabid idarah, kabid imarah, kabid riayah, traders, congregants, and the community. The results showed that Al-Islah Mosque applies managerial functions such as planning, organizing, implementing, and supervising the collection and distribution of fundraising funds managed by the Mosque Social Welfare Institution (LKSM). LKSM has full responsibility in social welfare activities, including mass circumcision, orphan compensation, corpse care, grief assistance, sacrificial arisan services, UPZISMABES, street vendors services, and blood donation. These programs have succeeded in improving the social welfare of the surrounding community with visible increases in employment, income, reduction in consumption expenditure, happiness of the dhuafa', easy access to education, health services, corpse care assistance, and free medical circumcisions.